Chemical Composition of Essential Oil of Teucrium orientale L. subsp. taylori (Boiss.) Rech. f. - H Amiri (Institue of Medicinal Plants, ACECR, 2008)
Background: The Teucrium genus belongs to Lamiaceae family and has 13 species in Iran. On the other hand the essential oils which are the plant's secondary metabolite products are widely used in food, pharmaceutical and cosmetic industry, as antibacterial and antioxidant products. Objective: Identification of the components of essential oil of Teucrium orientale L. subsp. taylori. and its comparison with Teucrium orientale L. subsp. orientale. Methods: This plant was collected from 55 Km. distant of Khoramabad at east of Lorestan province.Voucher specimens were deposited at the herbarium of Natural Resource and Agriculture Center of Lorestan Province (NO: 5783). The air-dried aerial parts were subjected to hydrodistillation method. Identification of essential oil constituents was made by GC and GC/MS. Results: Fourty components were identified in the essential oil and the main constituents were linalool (28.60%), caryophyllene oxide (15.62%), octanol (9.55%), β- pinene (8.75%), β- caryophyllene (7.33%), germacrene-D (4.60%) and 1,8-cineol (4.53%). Conclusion: The comparison of the obtained results from analysis of the oil of Teucrium orientale L. subsp. taylori in this research with other investigations on Teucrium orientale L. subsp. orientale showed that the main components in the oils of two subspecies with a few differences in percentages of the major constituents are similar. But in other components which constituentes lesser percentages of the essential oils, there are some differences. considering the similarities in the components of subspecies of oriental and tylori, perhaps these two subspecies will be placed under the same chemotypes.